Magnetohydrodynamic Free Stream and Heat Transfer of Nanofluid Flow Over an Exponentially Radiating Stretching Sheet With Variable Fluid Properties - Irfan, Muhammad; Farooq, Muhammad Asif; Iqra, Tousif (Frontiers in Physics, 2019)
This paper deals with the MHD free stream nanofluid flow and heat transfer over an exponentially radiating stretching sheet accompanied with variable fluid properties. By integrating appropriate similarity transformations, the fundamental governing partial differential equations (PDEs) are transformed into nonlinear ordinary differential equations. The resulting equations are successfully solved by using shooting method and MATLAB built-in solver bvp4c. The major effect of the skin friction coefficient, Nusselt number and Sherwood number on the flow field have been calculated. The alteration of fluid flow is governed by different parameters, magnetic parameter M, Prandtl number Pr, Lewis Number Le, thromophoresis paramter Nt, Brownian motion parameter Nb, radiation parameter Rd which are presented in tabulated format. Graphs are also plotted to observe the effects of different aforementioned parameters on velocity, temperature and concentration profiles.